Influence of Packaging on Consumers’ Buying Behaviour of Soft Drinks in Accra, Ghana - Ofosu-Boateng, Ibrahim (British Journal of Marketing Studies, 2019)
The study assesses the influence of packaging on consumers’ buying behaviour of soft drinks in Accra, Ghana. The objective of the study was to examine the forms of packaging used by the soft drink industry in Accra, Ghana; to find out the relationship between packaging and consumer buying behaviour in the soft drink industry in Accra, Ghana and to determine the elements of packaging influencing consumer buying behaviour in the soft drink industry in Accra, Ghana. The study adopted the survey design. Data were gathered from a convenient selected sample of 220 soft drink consumers in Accra, Ghana using a structured interview guide and data analyses carried out using SPSS version 20. The findings of the study revealed plastic bottles packaging ranked first, aluminium cans packaging ranked second, paper packaging ranked third and glass bottle packaging ranked fourth as forms of packaging used by the soft drink industry in Accra, Ghana. At another level, the study shows a significant relationship between packaging and consumer buying behaviour. Based on the findings, the study recommends the soft drink industry in Accra, Ghana to concentrate on the use of plastic, aluminium can and paper as forms of packaging to influence consumers’ buying behaviour whilst reducing the use of glass bottle packaging. Also, It is recommended that packaging should be given utmost priority by soft drink producers in Accra since it has a significant relationship with consumer buying behaviour; can act as a ‘silent salesperson’, helping consumers by bringing a particular brand to their attention